ChAOS Benthic Mega-Infauna abundance in the Arctic Ocean, summer 2017-2019. - Mesher, Thomas; McNeill, Caroline Louise; Nunes, Joana (NERC EDS British Oceanographic Data Centre NOC, 2021)
Benthic Mega-Infauna abundance and biomass data collected during a series of ship-board sampling campaigns in the Barents Sea. As part of the NERC funded Changing Arctic Ocean programme, in July of 2017, 2018 and 2019, the RSS James Clark Ross followed a North-South transect at 30 degrees Longitude. In 2017 six stations were sampled (B3, B13, B14, B15, B16, B17); in 2018 seven stations were sampled (B3, B13, B14, Xs, B15, B16, B17); and in 2019 five stations were sampled (B3, B13, B14, B15, B16). Megafaunal samples were collected using an SMBA corer (surface area 0.5m 2 ). On recovery all faunal samples were fixed and preserved with 10% buffered formaldehyde solution. The faunal samples were transported to Plymouth Marine Laboratory where the fauna were extracted, identified to species level where possible using the most up to date literature available, and biomassed (blotted wet weight) to species level. A reference collection has been created containing an example of each taxon to ensure maximum quality control was maintained by the three analysts that conducted the species identification and for subsequent cruise data generated.